MODEL REGRESI PENDAPATAN ASLI DAERAH BERDASARKAN PAJAK DAERAH, RETRIBUSI DAERAH DAN JUMLAH PENDUDUK PADA PROVINSI JAWA TIMUR (2018-2020) - Sari, Vinna Marlita (Universitas Nusantara PGRI Kediri, 2022)
This study uses a quantitative approach with the ex post facto method which aims to analyze and assess the impact of Regional Taxes, Regional Levies, and Populations on Regional Original Income in East Java Province in 2018–2020.Data analysis in this study used multiple linear regression using SPSS version 23 software. A total of 38 regencies and cities in East Java Province were sampled in this study. Regional Taxes, Regional Levies and Population Partially or Simultaneously affect Regional Original Income in East Java province.The latest data from the realization of Regional Original Income in 2018-2020 as well as a larger scope of research means that the Regency & City as a whole in East Java Province are used to update this research with previous research. This study uses a quantitative approach with the ex post facto method which aims to analyze and assess the impact of Regional Taxes, Regional Levies, and Populations on Regional Original Income in East Java Province in 2018–2020.Data analysis in this study used multiple linear regression using SPSS version 23 software. A total of 38 regencies and cities in East Java Province were sampled in this study. Regional Taxes, Regional Levies and Population Partially or Simultaneously affect Regional Original Income in East Java province.The latest data from the realization of Regional Original Income in 2018-2020 as well as a larger scope of research means that the Regency & City as a whole in East Java Province are used to update this research with previous research. update this research with previous research.